PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM IMPLEMENTASI PSIKOSOSIAL ERIKSON DI SEKOLAH - Caca Danuwijaya; Sulaiman; Rus'ansyah; Akhmad Maki; Nahdiyatul Husna (Fakultas Agama Islam Universitas Wiralodra, 2022)
THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN ERIKSON'S PSYCHOSOCIAL IMPLEMENTATION IN SCHOOL This study aims to determine Erikson's psychosocial and Islamic religious education teacher's role (PAI teacher) in its implementation in schools. In this study, a literacy study was used, through critical and in-depth evaluation of the results of previous research to find new understanding. Data were collected from various sources of relevant journals and books as well as daily experience, then content analysis was carried out through the stages of identification, evaluation, and interpretation. The research found: (1) Erikson's psychosocial consists of eight stages, each of which has its own crisis that needs to be addressed by the appropriate roles of teachers so that it has a positive effect on the next stage of psychosocial development; and (2) PAI teachers can determine appropriate and flexible roles, both uswah hasanah or role models, semi-participants, participators and evaluators, as well as motivators and supervisors in Erikson's psychosocial implementation in schools in the form of hablumminallah (divine/vertical interaction) and hablumminannas (interaction of divinity/vertical) humanitarian/social/horizontal). Thus, students can grow and develop normally and in balance to become mature human beings who are responsible and mature in accordance with their nature and expectations of all parties.